2010
DOI: 10.1007/s00299-010-0873-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of HsfA2 from Lily (Lilium longiflorum)

Abstract: Heat shock transcription factors (Hsfs) are the terminal components of the signal transduction chain mediating the activation of genes responsive to both heat stress and a large number of chemical stressors. This paper aims to clone Hsf from lily and characterize its function by analyses of mRNA expression, transactivation activity and thermotolerance of transgenic Arabidopsis. In this study, the gene encoding HsfA2 with 1,053 bp open reading frame (ORF) was cloned by rapid amplification of cDNA ends (RACE) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 43 publications
7
48
0
Order By: Relevance
“…The selection of reference gene(s) might influence the results or even conclusion of studies, especially those concerning plant development or stress response, as there would be more variation in gene expression under those conditions. As a commonly used reference gene, the ACT gene family associated with cell structure maintenance was previously used as the reference gene for normalization in Lilium (Wang et al, 2009; Xin et al, 2010), and it showed stable expression in L. davidii var. unicolor (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of reference gene(s) might influence the results or even conclusion of studies, especially those concerning plant development or stress response, as there would be more variation in gene expression under those conditions. As a commonly used reference gene, the ACT gene family associated with cell structure maintenance was previously used as the reference gene for normalization in Lilium (Wang et al, 2009; Xin et al, 2010), and it showed stable expression in L. davidii var. unicolor (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of cultivars in this genus were produced under inter-specific hybridization and artificial selection in the last twenty years. However, only a limited number of studies have been carried out on the gene expression of Lilium , and the reference genes used in these studies, namely ACT , 18S rRNA or GAPDH (He et al, 2014; Li et al, 2014; Tong et al, 2013; Wang et al, 2009; Xin et al, 2010), was only based on the results from other species without an experimental comparison among the candidate reference genes of Lilium . Only until very recently the evaluation of reference genes in L. davidii var.…”
Section: Introductionmentioning
confidence: 99%
“…The expression level in the heat-sensitive line B6 was higher than that in the heat-tolerant line R9 as a whole, which was not coherent with the heat tolerance ( Figure 5). Xin et al (2010) found that the HsfA2 expression in heat-tolerant cultivar leaves of Lilium longiflorum reached its peak 1 h after the heat treatment, and then it decreased slightly. In contrast, in the heat-sensitive cultivar, the expression peaked 12 h after the heat shock and then decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…All of these are important for the formation of plant thermotolerance (Schramm et al, 2006). Until now, the function of the gene HsfA2 in thermotolerance formation has been researched in Solanum lycopersicum (Scharf et al, 1993), Arabidopsis thaliana (Charng et al, 2007), Oryza sativa (Yokotani et al, 2008), and Lilium longiflorum (Xin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The moderate HAT stress may activate some thermo-tolerance genes to protect against severe HAT. A heat shock transcription factor gene called LlHsfA2, has been reported to play an important role in heat signalling pathway in lily and it has been demonstrated that overexpression of LlHsfA2 can increase the thermotolerance of transgenic Arabidopsis plants (Xin et al, 2010). This observation is strengthened by the fact that LlHSFA1 isolated from lily leaves and overexpressed in transgenic Arabidopsis gave similar results (Gong et al, 2014).…”
supporting
confidence: 71%